Valve arrangement of internal combustion engine. - Megat Ahmad, Megat Mohamad Hamdan; AusuBAmatov, Ryspek; Ismail, Napsiah; Yudie Sastra, Hasan; Abang Ali, Abang Abdullah; Radin Sohadie, Radin Umar (2004)

(untitled)
A valve arrangement system for internal combustion comprising at least one cylinder having engine piston operating within said cylinder; housing forming an enclosed combustion chamber in cooperation with said engine piston and having housing ports to said combustion chamber; a pair of bush with corresponding holes in communication with said housing ports, which is rotatably fitted within said housing; and driving means connected to said rotating bush for transferring rotary motions or linear reciprocation motions.